Evaluation of biological qualification by rapid diagnostic tests of transfused blood units in Isiro, DRC: Case of major virological markers - Matimada, Gertrude Mongila; Sumbu, Blaise Matondo Ma Nzambi; Misingi, Pacifique; Muamba Muamba, Corneille; Gamani, Diane Sare; Kpanya, Tacite; Hamunaki Masika, Lydie; Masidi Muwonga, Jérémie (Orapuh Journal, 2025)
Introduction Ensuring blood recipient safety during transfusion requires systematic screening for transfusion-transmissible infections (TTIs). In Isiro, this screening is performed using single-unit, operator-dependent rapid diagnostic tests (RDTs).PurposeThis study aimed to evaluate the virological qualification of transfused blood units in healthcare facilities in Isiro, Haut-Uélé Province, Democratic Republic of the Congo.MethodsA descriptive and analytical cross-sectional study was conducted from August 14, 2023, to September 13, 2023, across five major healthcare facilities in Isiro that perform blood transfusions. A counter-analysis was conducted at the National Blood Transfusion Center (CNTS) using the Architect i1000 automated system, which operates based on chemiluminescence, on samples collected in dry tubes. The intrinsic performance metrics, including sensitivity (Se) and specificity (Sp), as well as extrinsic performance measures such as positive predictive value (PPV) and negative predictive value (NPV), were estimated for the main virological markers (HIV, HBV, and HCV). Cohen's Kappa coefficient was used to assess the reliability of RDTs compared to the Architect i1000.ResultsA total of 148 samples were collected during the study period. The mean age of the study population was 32.92 ± 8.43 years, with a modal age of 28 years. The minimum and maximum ages recorded were 18 and 55 years, respectively. Most donors were family donors, with a male-to-female sex ratio of 1.85. The frequency of infectious markers for HIV, HBV, and HCV was 2%, 3.4%, and 4.1%, respectively. The sensitivity of RDTs was low. The agreement between RDTs and the Architect i1000 was assessed as moderate (56.1%), good (65.6%), and moderate (42.9%) for HIV-1/2 antibodies, HBs antigen, and HCV antibodies, respectively.ConclusionBlood qualified using RDTs in Isiro exposes recipients to a risk of contracting TTIs. Further studies to better understand the problem, additional training for healthcare providers, and more effective tests are necessary to prevent contamination through blood transfusions.